Medium-scale heat fluxes across the antarctic circumpolar current in the drake passage and western Scotia Sea - Piola, A.R.; Grasselli, M.B.
Closely spaced continuous temperature profiles from expendable bathythermographs launched along two sections across the Drake Passage and western Scotia Sea in the summer 1981-1982 are used to examine the vertical medium-scale (~10-100 m) temperature fine structure. The large-scale temperature structure across the frontal regimes characteristic of the Antarctic Circumpolar Current and the cross-frontal structure of the upper ocean are discussed. In the Drake Passage the heat content drops about 0.5 x 102 Kcal cm-2 (2 x 109 J m-2) across the Subantarctic Zone and 0.9 x 102 Kcal cm-2 (3.6 x 109 J m-2) across the Polar Front. In the Scotia Sea the heat content changes across the front are not as prominent. The statistical model of Joyce (1977) is used to quantify the heat fluxes across the fronts produced by the medium-scale temperature interleaving. In the Drake Passage the estimated heat flux is 0.32 x 10-3 °C m s-1 (1.3 x 103 W m-2) across the Subantarctic Front and 0.46 x 10-3 °C m s-1 (1.9 x 103 W m-2) across the Polar Front. In the Scotia Sea the estimated heat flux is larger in the Polar Front reaching 0.71 x 10-3 °C m s-1 (2.9 x 103 W m-2). The medium-scale fine structure heat fluxes are about 10% of the existing estimates of the mesoscale eddy heat fluxes and comparable to heat fluxes associated with the meridional flow of deep and bottom waters across the Antarctic Circumpolar Current.